ISTIKHDAMU AL MUNAQOSYAH ‘ABRO AL INTIRNIT FI AT TA’LIM MAHARA AL KITABAH LILHULULI ‘ALA FUQDANI AT TA’ALLUM (DIROSAT HALATI FI QISMI AT TA’LIM AT TARBIYAH AL ISLAMIYAH ‘AN B’UD BI JAMI’ATI SYEKH NURJATI CIREBON) - Anwar, Mohammad Shohibul; Ulum, Muhammad Samsul; Maghfiroh, Rodiatul; Hamidah, Noor Zinatul; Munir, Muhammad Syahrul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This research responds to the urgency of using technology as an online discussion forum in distance learning, especially in Arabic writing skills at PJJ PAI IAIN Syekh Nurjati Cirebon, Indonesia as a step in overcoming learning loss challenges that often arise in online learning. This study aims to explore the application of online discussions and analyze student responses to their application in Arabic writing skills learning at PJJ PAI IAIN Syekh Nurjati Cirebon. The research method uses a qualitative approach by applying interviews and content analysis to data from students involved in learning Arabic writing skills. The findings of this study reflect the diverse responses of students to the use of online discussions. Comprehension of the material experienced varying improvements, while writing skills showed mixed development among participants. Students' active participation in online discussions creates different learning dynamics. This research provides a comprehensive overview of student responses to this learning method, providing valuable insights for developing better learning approaches in a distance learning environment.